Investigation of superlattice structure parameters using quasi-forbidden reflections - Kladko, V.P.; Datsenko, L.I.; Korchovyi, A.A.; Machulin, V.F.; Lytvyn, P.M.; Shalimov, A.V.; Kuchuk, A.V.; Kogutyuk, P.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
We studied possibilities of a nondestructive X-ray technique for testing short-period strained GaAs-AlAs superlattices. An analysis of the quasi-forbidden 200 reflections may be used for determination of superlattice layer structure parameters and sublayer thickness. The effect of irregularity of superlattice transition region on X-ray diffraction reflection curves and elastic strains in layers was studied.